SPEAKING IN RANK: A COMPARATIVE ETHNOGRAPHIC ANALYSIS OF HIERARCHICAL LANGUAGE PRACTICES IN JAVANESE AND JAPANESE CULTURES - Dewi Pangestu Said; Kenfitria Diah Wijayanti; Favorita Kurwidaria; Astiana Ajeng Rahadini; Prima Veronika; Nirbito Hanggoro Pribadi; Eni Sri Budi Lestari (Universitas Sebelas Maret, 2025)
This study examines how hierarchical values are expressed and maintained through language in both Javanese and Japanese societies. Its goal is to explore the role of language in articulating and reinforcing social stratification in two different cultural settings. Using a comparative ethnographic approach, the study examines how these linguistic systems function within their respective socio-cultural contexts. The results show that both languages employ language codes heavily influenced by factors such as age, social status, and proximity between individuals. This linguistic practice not only functions as a marker of politeness but also as a tool to manage power dynamics and uphold traditional norms. The discussion highlights how language choices serve as mechanisms for asserting social standing and shaping identities within hierarchical structures. In conclusion, this article demonstrates that understanding language practices provides valuable information about cultural concepts, emphasizing respect and obedience within social hierarchies. It also advocates for further cross-cultural research to deepen the understanding of how language reflects and influences social hierarchies.